1980
DOI: 10.1128/iai.30.1.90-98.1980
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma-dependent activation of normal mouse lymphocytes: requirement for functional T lymphocytes in the cytotoxicity reaction mediated by Mycoplasma arthritidis

Abstract: Syngeneic and allogeneic target cells were killed in the presence of CBA mouse lymphocytes and viable Mycoplasma arthritidis. Medium supplementation had no effect on the response. Nonviable M. arthritidis was also capable of stimulating lymphocytotoxicity, although to a much lesser extent. Cytotoxicity was shown to be largely dependent upon the lymphocytes, since lymphocytes preincubated with mycoplasmas and treated to remove remaining organisms were highly toxic to target cells, whereas supernatants prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1982
1982
1994
1994

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…It is of particular interest that several recent studies that used Mycoplasma species to generate CMC against syngeneic fibroblasts have led to very similar results (1,13). In particular, Mycoplasma species have also been identified as B-cell mitogens (3,13,28), have been recognized as inducing the generation of cytotoxic lymphocytes requiring prolonged contact with syngeneic target cells for expression of cytotoxicity (14), and have been recognized as triggering the generation of cytotoxic lymphocytes after only brief exposure (13).…”
Section: Discussionmentioning
confidence: 94%
“…It is of particular interest that several recent studies that used Mycoplasma species to generate CMC against syngeneic fibroblasts have led to very similar results (1,13). In particular, Mycoplasma species have also been identified as B-cell mitogens (3,13,28), have been recognized as inducing the generation of cytotoxic lymphocytes requiring prolonged contact with syngeneic target cells for expression of cytotoxicity (14), and have been recognized as triggering the generation of cytotoxic lymphocytes after only brief exposure (13).…”
Section: Discussionmentioning
confidence: 94%
“…We observed that heated organisms tend to become stickier after treatment, and it is possible that sensitization with these organisms is due to nonspecific sticking to the cell surface. Mycoplasma arthritidis have been reported to sensitize cells to become cytotoxic effectors (7). It was suggested that the mycoplasmas, which bind to the surface of cells, may function as a glue, binding target cells to lymphocytes with preexisting cytotoxic potential.…”
Section: Vol 35 1982mentioning
confidence: 99%
“…Indeed, mycoplasmas induce proliferation and immunoglobulin secretion of both resting and activated B lymphocytes (3,22,24). Various mycoplasma species behave as T-cell mitogens and induce the formation of cytotoxic T cells (6,17). Mycoplasma also induces macrophage-mediated cytolysis (10,30).…”
mentioning
confidence: 99%